Non-ideal magnetohydrodynamics on a moving mesh - Marinacci, Federico; Vogelsberger, Mark; Kannan, Rahul; Mocz, Philip; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. In certain astrophysical systems, the commonly employed ideal magnetohydrodynamics (MHD) approximation breaks down. Here, we introduce novel explicit